Prostate-Specific Antigen Kinetics Effects on Outcomes of Low-Volume Metastatic Prostate Cancer Patients Receiving Androgen Deprivation Therapy. (27th August 2021) - Lin, Yen-Chi; Lin, Po-Hung; Shao, I-Hung; Chu, Yuan-Cheng; Kan, Hung-Cheng; Liu, Chung-Yi; Yu, Kai-Jie; Chang, Ying-Hsu; Pang, See-Tong; Huang, Jhen-Ling; Chuang, Cheng-Keng
Abstract : Background . The present study aimed to analyse factors influencing the effects of androgen deprivation therapy (ADT) in patients with newly diagnosed metastatic castration-naïve prostate cancer (mCNPC), especially in low-volume disease (LVD), according to subclassification of metastatic prostate cancer established by the CHAARTED trial. Materials and Methods . We reviewed 648 patients with newly diagnosed mCNPC receiving ADT at Chang Gung Memorial Hospital from January 2007 to December 2016. Basic characteristics and PSA kinetics profile were subsequently evaluated. Results . 48.3% of LVD patients progressed to castration-resistant prostate cancer (mCRPC). Among them, CRPC group had significantly shorter time to PSA nadir (TTN) and faster time from PSA nadir to CRPC (TFNTC) (p < 0.001) compared to non-CRPC group. PSA doubling time (PSADT) < 4 months tended to be associated with faster disease progression and shorter overall survival (OS). Among all patients with metastatic prostate cancer, those with shorter TTN <9 months, higher nadir PSA level ≥1 ng/mL, and shorter PSADT <3 months had increased tendency for biochemical progression. Conclusions . PSADT is an effective clinical predictor for disease progression and survival in LVD. Other PSA kinetics including TTN and TFNTC, though not the major predictors for disease progression or OS in LVD, might be the predictors for disease control status.